Ensino da dança na escola: enfrentamentos e barreiras a transpor - Coqueiro Pires de Sousa, Nilza (2019)
Dance is one of the most traditional socio-cultural manifestations present in the communities from the earliest days of humanity to the present days. Nonetheless, in the context of the education system, it faces many challenges in the scope of teaching and the student learning process. Thus, in the present action-research, with a group of Physical Education, Art and Pedagogy teachers, the aim was to analyze the confrontations and the barriers to overcome, detecting what is decisive in the teaching and learning process of teaching dance for school students. The methodology focused on the mixed (qualitative-quantitative) approach, using for data collection the questionnaire, semi-structured interview and oral and written reports. The results were discussed and articulated in the review of the literature, through descriptive statistical procedures and content analysis. It was verified: a) internal confrontations: predominance of the lack of didactic-pedagogical materials and inadequate school infrastructure; b) qualification and scientific-methodological knowledge: insufficient academic preparation and mastery of content in educational dance; and c) external interferences: religion and the media. It was concluded that a revision of the political-pedagogical projects and, consequently, a decision of the school team to recognize the meaning of the teaching and the learning process of dance in the integral and differentiated formation of the student is imperative.